Differential neonatal testosterone imprinting of GH-dependent liver proteins and genes in female mice - Ramirez, Maria Cecilia (2010)
bnormal exposure to steroid hormones within a critical developmental period elicits permanent alterations in female reproductive physiology in rodents, but the impact on the female GH axis and the underlying sexual differences in hepatic enzymes have not been described in detail. We have investigated the effect of neonatal androgenization of female mice (achieved by s.c. injection of 100 mg testosterone propionate (TP) on the day of birth: TP females) on the GHRH–somatostatin–GH axis and downstream GH targets, which included female and male predominant liver enzymes and secreted proteins. At 4 months of age, an organizational effect of neonatal testosterone was evidenced on hypothalamic Ghrh mRNA level but not on somatostatin (stt) mRNA level. Ghrh mRNA levels were higher in males than in females, but not in TP females. Increased expression in TP females correlated with increased pituitary GH content and somatotrope population, increased serum and liver IGF-I concentration, and ultimately higher body weight. Murine urinary proteins (MUPs) that were excreted at higher levels in male urine, and whose expression requires pulsatile occupancy of liver GH receptors, were not modified in TP females and neither was liver Mup 1/2/6/8 mRNA expression. Furthermore, a male predominant liver gene (Cyp2d9) was not masculinized in TP females either, whereas two female predominant genes (Cyp2b9 and Cyp2a4) were defeminized. These data support the hypothesis that neonatal steroid exposure contributes to the remodeling of the GH axis and defeminization of hepatic steroid-metabolizing enzymes, which may compromise liver physiology.